Prevention and Treatment of Intestinal Polyps based on the Theory of "Yang Hua Qi, Yin Shaping" - Huang, Jinyuan; Xi, Jianping; Yuan, Min; Wang, Yubin (Journal of Contemporary Medical Practice, 2024)
Intestinal polyp is a common digestive system disease, and its incidence is increasing, among which adenomatous polyp is the main type of precancerous transformation of colorectal cancer. In traditional Chinese medicine, this can be classified as "intestinal mushroom" or "accumulation" and other diseases. "Yang transforming qi and yin forming" means that yang dominates qi, while yin dominates the body, which shows the balance of their interaction and unity of opposites. Traditional Chinese medicine believes that the imbalance between yin and yang is the basic pathogenesis of the disease. Based on this discussion of the understanding of intestinal polyps, it is considered that the disease is based on the deficiency of Yang qi, and Yin formation is the sign of the disease. Therefore, the clinical treatment should be based on warming Yang Qi, dispelling phlegm and removing blood stasis to eliminate Yin and Nebula, and to regulate Qi, so as to make the body reach the state of Yin Pingyang.